Evaluación del impacto ambiental de cuatro estrategias de manejo, para el control del psílido de la papa (Bactericera cockerelli), en el cultivo de papa (Solanun tuberosum l.) variedad superchola ubicado en el cantón mejía, estación experimental santa catalina 2020. - Saltos Pérez, Brayan Estiven (2020)
The research was focused on the environmental impact of using chemical strategies to control potato psyllid (Bactericera Cockerelli) (Bc), because this pest can generate 100% losses of the crop, so farmers have been forced to use various pesticides for control, the purpose of research is to evaluate the environmental impact of four chemical strategies for the management of potato psyllid, Using methodologies applied to agriculture such as the calculation of the Environmental Impact Rate (EIR), proposed by Kovach and the survey of the Leopold matrix, the trial was carried out at the International Potato Center (CIP), located in the Parish of Cutuglagua, Santa Catalina Experimental Station at 3058 meters above sea level, with the results that the strategy with the greatest environmental impact with a value of 125.50% was strategy four, while strategy three is more environmentally friendly with a value of 60.35%; With regard to the Leopold matrix, the strategy that had the greatest impact on the environment with an algebraic sum of -3509 was strategy two and the strategy with the least impact was strategy three with a sum of -2835; with regard to costs, strategy two represented a greater investment in production per hectare with a value of $3914. 90, followed by strategy one with a value of $3664.26, strategy three with $3594.89 and finally strategy four with a value of $3461.91